Prospective Trial of an Herbal Formula BYSH and Saw Palmetto in Patients with Hormonal Refractory Prostate Cancer: A Pilot Study - C.-F. Ng, Anthony; Cheng, K.-F.; Leung, P.-C. (Recent Patents on Inflammation & Allergy Drug Discovery, 2014)
Objective: BYSH, a herbal formula, was evaluated for efficacy and safety in a pilot study for patients with advanced hormone refractory prostate cancer (HRPC). Patients and Methods: The pilot study was designed as a singlecenter open-label trial. Patients with HRPC were treated with BYSH for 24 weeks. The primary end point was the changes in serum prostate-specific antigen (PSA) level. Safety parameters such as liver and renal functions were monitored during the study period. Results: Ten patients were eligible for the study. Most of them had stable PSA levels while taking BYSH. However, at the end of the BYSH treatment, the level of PSA increased. The median survival from diagnosis of HRPC was 16.4 months. Liver and renal functions remained normal. BYSH was well tolerated and no patient reported adverse events during the study period. Conclusion: Although it is inappropriate to make a conclusion based on the pilot study results, the trend of improvement is obvious. Further investigations should be conducted to demonstrate its clinical benefits. We have also briefly reviewed some plant products which are patented and also available in market.
Keywords: prostate cancer